Thinking in Silence: Cognitive Pauses and Their Role in Second Language Sentence Planning - Loudya Putri Utama; Miftahul Jannah; Raudhotul Fadhilah; Yani Lubis (International Journal Multidisciplinary Science, 2026)
Silent pauses are a frequent feature of second language speech, yet they are often interpreted as signs of low fluency. This study examines silent pauses from a psycholinguistic perspective by focusing on their role in second language sentence planning. Using a qualitative design, the study involved ten undergraduate EFL learners and collected data through oral sentence production tasks and stimulated recall interviews. Speech data were recorded and analyzed to identify silent pauses occurring before and during sentence production, while interview data were used to explore learners’ cognitive processes during these pauses. The findings show that silent pauses function as cognitive resources that support conceptual planning, lexical retrieval, and syntactic organization. Learners used silence deliberately to manage cognitive load and maintain accuracy, although these pauses were often perceived negatively due to pressure to speak fluently. The study reinforces staged models of speech production and challenges narrow definitions of fluency by highlighting silence as an integral part of second language processing. Pedagogically, the findings emphasize the importance of providing thinking time to support more accurate and complex language use.